Students Reflection Toward the Application of Peer Assessment Activity by Using Moodle-Based Workshop to Empower Learning Autonomy - Abdul Rosyid; Lungguh Halira Vonti (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This research is an endeavor to portrait an effort to empower learners’ autonomy through peer assessment activity by using Moodle-based workshop. The method employed in this study was descriptive case study. 30 students taken from one class were involved in this study as the participants. The data of the research was gathered through administering questionnaire and conducting focused group discussion. The instruments were designed to find the answer of the following question, i.e., to what extend does peer assessment activity using Moodle-based workshop empower learning autonomy? Peer assessment activity was applied in Text Based Structure Class focusing on the topic about English Clauses. Autonomous learning indicators that become the focus of this research are: a) determining the objectives, b) defining the content and the progress of learning, c) selecting appropriate methods and techniques, d) monitoring the applied techniques methods, and e) evaluating what has been achieved. The findings of this study reveal that peer assessment activity by using Moodle-based workshop can promote learners’ autonomy. It is also discovered that the learners are able to learn from the exchanging inputs activities with their peers and most importantly they can access and review the inputs anywhere and anytime they desire.